Aqueous synthesis and antibacterial activity of Silver nanoparticles against pseudomonas putida. (2019) - Sarkar, Rajat; Anil Kumar, C.; Kumbhakar, Pathik; Mandal, Tamal
Abstract: Aqueous synthesis of silver nanoparticles (NPs) is gaining importance as their biocompatibility and eco-friendly nature. However, in this work, we have reported aqueous synthesis of silver NPs through a chemical route and studied its bio compatibility with pseudomonas putida . The prepared nanostructures have been analyzed by using high resolution transmission electron microscope (HRTEM), selected-area electron diffraction (SAED), Energy-dispersive spectra (EDS), UV-visible spectrophotometer and photoluminescence (PL) spectroflourimeter. It is found that the synthesized materials exhibit an absorption peak at ∼ 420 nm and it is the characteristic surface plasmon resonance peak in silver NPs. It is found from HRTEM measurement that the synthesized NPs are spherical in shape and the average particle size is 2.5 nm. The synthesized samples show strong PL emission in the UV region below 400 nm. Antimicrobial effect of silver NPs for Pseudomonas putida is investigated by using disk diffusion method. The prepared silver NPs exhibit strong antimicrobial activity against Pseudomonas putida at concentrations ranging between 90µg/ml to 170µg/ml for 24 hours. Thus it may be concluded that silver NPs can be used as effective antimicrobial control systems upto 130 µg/ml